2024
DOI: 10.3390/bioengineering11010048
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Dual-Wavelength Laser Irradiation against Implant-Adherent Biofilms of Staphylococcus aureus, Escherichia coli, and Candida albicans for Improved Antimicrobial Photodynamic Therapy

Shima Afrasiabi,
Stefano Benedicenti,
Antonio Signore
et al.

Abstract: The efficiency of antimicrobial photodynamic therapy (PDT) might be improved by using multiple wavelengths. This study investigates the sensitivity of implant-adherent biofilms of Staphylococcus aureus, Escherichia coli, and Candida albicans to indocyanine green (ICG)-808 nm diode laser, toluidine blue O (TBO)-635 nm diode laser, and hydrogen peroxide (HP)-980 nm diode laser and their combination when irradiated with dual-wavelength laser irradiation (simultaneously 980–635 nm or 980–808 nm). After an incubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Similarly, Sousa et al [22] achieved better results with chemical treatment with sodium hypochlorite and chlorhexidine after mechanical cleaning with a titanium brush. The results of the aforementioned studies show that using a chemical agent in addition to mechanical biofilm removal can improve the decontamination of the implant surface [22,30,31]. This is in accordance with the results of our study, where after treatment with a chitosan brush and chlorhexidine, fewer bacteria were found than if a chitosan brush was used alone.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, Sousa et al [22] achieved better results with chemical treatment with sodium hypochlorite and chlorhexidine after mechanical cleaning with a titanium brush. The results of the aforementioned studies show that using a chemical agent in addition to mechanical biofilm removal can improve the decontamination of the implant surface [22,30,31]. This is in accordance with the results of our study, where after treatment with a chitosan brush and chlorhexidine, fewer bacteria were found than if a chitosan brush was used alone.…”
Section: Discussionsupporting
confidence: 92%
“…Although different concentrations of chlorhexidine were used, i.e., in their research, 0.12%, and in ours, 0.20%, the chlorhexidine reduced the number of bacteria on the implant surface. Afrasiabi et al showed that the combined use of hydrogen peroxide with a photosensitizer and photodynamic therapy has a more efficient antibacterial effect on biofilms of Staphylococcus aureus, Escherichia coli and Candida albicans compared to each treatment alone [31]. Similarly, Sousa et al [22] achieved better results with chemical treatment with sodium hypochlorite and chlorhexidine after mechanical cleaning with a titanium brush.…”
Section: Discussionmentioning
confidence: 99%